Peran, Tugas dan Tanggung Jawab Manajemen Pendidikan - Baslini, Baslini (Yayasan Sembilan Pemuda Indonesia, 2022)
The purpose of this study was to determine the duties, functions, and responsibilities of education management. This study elaborates the theoretical and practical basis on the importance of the principal's role in managing education both in terms of duties, functions, and responsibilities. The methodology or approach used in this paper uses a library research method or approach, while data collection is carried out by reviewing and exploring several journals, books, and documents (both printed and electronic) as well as sources of data and or other information. deemed relevant to the study. The data analysis technique used is content analysis. To maintain the accuracy of the assessment and prevent misinformation in data analysis, inter-library checking and rereading of the literature are carried out.